Fungibility, labels, and consumption - Johannes Abeler; Felix Marklein (Institute for the Study of Labor (IZA), 2008)
Fungibility of money is a central principle in economics. It implies that any unit of money is substitutable for another and that the composition of income is irrelevant for consumption. We find in a field experiment that even in a simple, incentivized setup many subjects do not treat money as fungible. When a label is attached to a part of their budget, subjects change consumption according to the suggestion of the label. A controlled laboratory experiment confirms this result and further shows that subjects with lower mathematical abilities are more likely to violate fungibility. The findings lend support to behavioral models such as narrow bracketing or mental accounting. One implication of our results is that in-kind benefits distort consumption more than usually assumed.
urn:nbn:de:101:1-20080527206
Keywords: C91; 330; Fungibility; In-kind benefits; mental accounting; inframarginal consumers; field experiment; laboratory experiment; Geld; Kognition; Konsumentenverhalten; Verhaltensökonomik; Test; Sachtransfer; Feldforschung; Theorie; Deutschland